2021
DOI: 10.1038/s41390-021-01456-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-resuscitation fluid in excess of hydration requirements is associated with higher mortality in critically ill children

Abstract: BACKGROUND: Large volumes of non-resuscitation fluids are often administered to critically ill children. We hypothesize that excess maintenance fluid is a significant contributor to non-resuscitation fluid and that non-resuscitation fluid administered beyond hydration requirements is associated with worse clinical outcomes in critically ill children. METHODS: We evaluated all patients admitted to two large urban pediatric intensive care units (PICU) between January 2010-August 2016 and January 2010-August 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The most common reason for admission was respiratory failure or distress (76/259, 29%) and postoperative monitoring and support (64/259, 25%). The median PICU day on which providers estimated fluid administration was 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common reason for admission was respiratory failure or distress (76/259, 29%) and postoperative monitoring and support (64/259, 25%). The median PICU day on which providers estimated fluid administration was 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that patients often receive fluids well beyond estimated hydration needs, but due to their retrospective design, have failed to identify whether clinicians actively prescribed more fluids than needed. 8,9,[22][23][24] Taken together, these data suggest that clinicians are generally unaware of how much fluid has been prescribed to their patients and further study into modifying prescribing behavior may impact care to patients at the bedside. Clinician accuracy varied by clinician role in the PICU in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another high-risk organ dysfunction interaction in our cohort, respiratory and renal dysfunction, has been described in critically ill children, particularly in the context of fluid overload. Existing literature has linked fluid overload with respiratory failure (particularly in the form of increased ventilator days) and mortality ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%